Pengembangan Model Diklat Blended Learning Untuk Peningkatan Kompetensi Pengelolaan PAUD di Balai Pengembangan PAUD Dan Pendidikan Masyarakat Provinsi Lampung - Nasib Wasito; R Riswandi; H Herpratiwi (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
The purpose of this study is to describe the blended learning education and training model to improve PAUD management competence at the PAUD development and community education center in Lampung province. This type of research is Research and Development (R&D) with the development model used is the development of the Dick & Carey model. The research was conducted at the Center for PAUD development and community education in Lampung Province. The instruments used to obtain data include interview guidelines, observation sheets, and questionnaire sheets. The analysis used is descriptive analysis by making a validation analysis of the product developed and an analysis of increasing competence. The results showed that the resulting product development in the form of a blended learning training model to improve the competence of PAUD managers was feasible and attractive and effectively applied in the PAUD development center and community education in Lampung province.